Magnetic-Field-Editable Wireless Power Transfer System With DD2 Magnetic Couplers for Position Detection and Misalignment Tolerance - Xuxing Duan; Wei Han; Youhao Hu; Hanlei Tian; Jinliang Huang; Zhen Zhang (IEEE Open Journal of Power Electronics)
Misalignment tolerance and receiver positioning are critical in designing wireless charging systems for electric vehicles. This study presents a magnetic field editable wireless power transfer (MFE-WPT) system equipped with the orthogonally-stacked double-D (DD2) magnetic coupler and a new control strategy, equivalently modifying the magnetic field distribution to tolerate misalignments without physically adjusting the receiver position. In this paper, the detailed analysis of circuit modeling, transfer characteristics, magnetic field distribution and position recognition strategy of the MEF-WPT system are given. Besides, an experimental prototype with the output power of 2.3 kW and the system efficiency of 87.99% has been built and four different receiver positions are selected to validate the effectiveness of the proposed system. By comparing with the traditional DD coil based WPT system, the measured results of the proposed system can maximumly improve the output power and system efficiency up to 2667.39% and 62.29%, when the receiver misalignment happens in the 200 × 200 mm charging plane.